Donošenje, produktivnost vode i ekonomski povratak paradajza natopljenog deficitom u Kaduni, Nigerija - Onwuegbunam, Donatus; Oyebode, Muyideen Abubakar; Igbadun, Henry Evonameh; Ismail, Habibu (Journal of Agricultural Sciences (Belgrade), 2023)
Abstract: Compared to gravity flow systems, pressurized drip irrigation provides a more efficient control on the amount of water applied, better irrigation uniformity and a higher initial capital and operation cost. Hence, an economic analysis is required to determine its profitability over a projected time. Field experiments were conducted in Afaka, Kaduna, Nigeria during two dry seasons of 2018 and 2019 to determine the effect of regulated deficit irrigation on the yield, crop water productivity and projected economic returns of UC 82B tomato, under pressurized drip irrigation. The economic returns were evaluated using benefit-cost ratio, net present values and payback period analyses. The highest fresh fruit yield (19.0 t/ha) was obtained in the full irrigation treatment (T1) while the highest crop water productivity (4.94 kg/m3) was obtained in the deficit treatment with full irrigation treatment at vegetative and flowering stages, then  60% of reference evapotranspiration at maturity (T7). The project was found to be profitable over the projected years, having benefit-cost ratios of 1.90 and 1.69; payback periods of 2.7 and 3.2 years, for T1 and T7, respectively. The full irrigation of tomato was therefore found to be more economically viable in the area than deficit irrigation, water not being considered as a limiting factor in terms of cost. Gravity drip irrigation was recommended to reduce the pumping cost of irrigation and thereby increase the profit margin.Keywords: Drip-irrigated, tomato, yield, water productivity, economic return, Nigeria